2006
DOI: 10.1901/jaba.2006.124-05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Undergarment Type on the Urinary Continence of Toddlers

Abstract: There is a growing trend toward later toilet training of typically developing children. This trend is a problem for caregivers and professionals who work with young children, because it is associated with a number of costs and health risks in child-care settings. Results of a recent study (Tarbox, Williams, & Friman, 2004) suggest that wearing underwear may facilitate the development of toileting skills. Based on these findings, we examined the effects of wearing disposable diapers, disposable pull-on training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Four children experienced the underwear component following baseline, and two of them showed overall improvements in performance (a 50% success rate). Simon and Thompson () used procedures similar to those in this study and found clear improvements in performance for two of five children (a 40% success rate).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Four children experienced the underwear component following baseline, and two of them showed overall improvements in performance (a 50% success rate). Simon and Thompson () used procedures similar to those in this study and found clear improvements in performance for two of five children (a 40% success rate).…”
Section: Discussionmentioning
confidence: 63%
“…For example, Tarbox, Williams, and Friman () found decreases in accidents and increases in appropriate eliminations when diapers were removed for an adult with an intellectual disability. Simon and Thompson () extended Tarbox et al by demonstrating improvements in toileting performance when typically developing children wore underwear instead of diapers. Two of five children had fewer accidents and increased appropriate eliminations while they wore underwear, and a third child's performance improved when underwear use followed increased fluids and longer sits on the toilet.…”
mentioning
confidence: 90%
“…The NAEYC also recognizes that it may be necessary to use a variety of teaching strategies to promote learning, including differential reinforcement (Bredekamp & Copple, 1997). Therefore, early childhood educators may implement reinforcement programs to promote acquisition of age-appropriate skills (e.g., continence, Simon & Thompson, 2006;social skills, Zanolli, Paden, & Cox, 1997). However, the literature says little about what strategies early childhood educators use to select reinforcers, and only a few behavior-analytic studies have described preference assessments developed for young children in early education (see, e.g., Hanley, Cammilleri, Tiger, & Ingvarsson, 2005;Reid, DiCarlo, Schepis, Hawkins, & Stricklin, 2003).…”
mentioning
confidence: 99%
“…[2][3][4][5] Procedures Two authors (A.C.G. PsychINFO search limiters included Search Mode, Boolean/Phrase; Publication Type, Peer Reviewed Journal; and Age Groups, Childhood (birth-12 yr).…”
Section: Literature Searchmentioning
confidence: 99%
“…[2][3][4][5] Their participants (n 5 34; aged 20-36 mo) were toilet trained within an average of 3.9 hours and remained continent with near-zero occurrence of accidents during a 4-month follow-up. [2][3][4][5] Their participants (n 5 34; aged 20-36 mo) were toilet trained within an average of 3.9 hours and remained continent with near-zero occurrence of accidents during a 4-month follow-up.…”
mentioning
confidence: 99%